PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH 8 PADA MATA PELAJARAN IPAS UNTUK PEMBELAJARAN SISWA SD KELAS 5 SD 1 MLATNOROWITO KUDUS - Naftali, Muhammad Baron; Muhammad Ali Yusuf; Agung Adi Saputra; Moch. Khabibur Rizal; Ika Ari Pratiwi (CV. Denasya Smart Publisher, 2025)
Education in the digital era demands innovation in the learning process, especially for abstract topics such as the solar system. This study aims to develop interactive learning media based on Macromedia Flash 8 for teaching the planets in the solar system within the Natural and Social Sciences (IPAS) subject for fifth-grade students at SD 1 Mlatinorowito Kudus. The method used is the Research and Development (R&D) approach following a simplified Borg and Gall model, which consists of six stages, starting from identifying potentials and problems to product testing. The research subjects included content experts, media experts, language experts, and fifth-grade students. Research instruments included expert validation questionnaires and student response questionnaires, used to assess the feasibility of the media and user feedback. Data analysis was carried out quantitatively using a Likert scale and converted into percentages. The results of expert validation indicated that the learning media was highly feasible with an average score above 80%, while student responses showed a high level of satisfaction and learning motivation, exceeding 85%. This learning media proved effective in enhancing students’ understanding of solar system concepts and motivating them to learn actively and independently. Therefore, the development of learning media based on Macromedia Flash 8 can serve as an innovative alternative to improve the quality of learning in elementary schools, particularly for subjects that require high levels of visualization and interactivity